On regularity of generalized solutions of the third boundary-value problem for an elliptic difference-differential equation - Tsvetkov, E. L. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
Unlike the case of elliptic differential equations, generalized solutions of elliptic difference-differential equations may be not smooth in a domainQ but remain smooth only in certain subdomainsQ r ⊂Q Conditions are considered which are necessary and sufficient for generalized solutions of the third boundary-value problem to preserve smoothness on the boundary of adjacent subdomainsQ r .